Ba4GaN3O - Hashimoto, Takayuki; Yamane, Hisanori (Acta crystallographica. Section E, Structure reports online, 2014)
Red transparant platelet-shaped single crystals of tetra-barium gallium trinitride oxide, Ba4GaN3O, were synthesized by the Na flux method. The crystal structure is isotypic with Sr4GaN3O, containing isolated triangular [GaN3](6-) anionic groups. O(2-) atoms are inserted between the slabs of [Ba4GaN3](2+), in which the [GaN3](6-) groups are surrounded by Ba(2+) atoms.